ETHICAL VIEWS OF ABDULLA AVLONI (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article explores the educational and moral views of the great Uzbek enlightener Abdulla Avloniy. It highlights his invaluable contribution to the formation of a modern approach to education and the spiritual development of youth. The author emphasizes the importance of harmonizing moral upbringing with formal education, drawing upon Avloniy’s works, particularly "Turkish Rose or Ethics." The article examines how Avloniy considered enlightenment, freedom, and ethical behavior to be central values in personal and societal progress. His views remain relevant today in addressing the challenges of modern education, moral threats, and youth development in a rapidly changing world. The article advocates for a national commitment to education as a means of building a prosperous and conscious society.